Evaluation of body weight and morphometric characteristics of the young queen of Apis cerana javana at different queen cup cell sizes - DEWI MASYITHOH; INGGIT KENTJONOWATY; SURAYA MOHAMAD SALLEH; USTADI USTADI; AGUSSALIM AGUSSALIM; FIQIH SHOLINA NASTAIN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Masyithoh D, Kentjonowaty I, Salleh SM, Ustadi, Agussalim, Nastain FS. 2023. Evaluation of body weight and morphometric characteristics of the young queen of Apis cerana javana at different queen cup cell sizes. Biodiversitas 24: 5626-5633. This study investigates body weight and morphometric characteristics of Apis cerana javana queen rearing based on differences in the queen cup sizes. The queen cell sizes were divided into three categories; the first group was a small category (T1) with a height of 0.75 cm, top diameter of 0.65 cm, and bottom diameter of 0.44 cm. The second treatment was medium category (T2) with a height of 0.85 cm, a top diameter of 0.71 cm, and a bottom diameter of 0.54 cm. The third treatment was a large category (T3) with a height of 1.00 cm, a top diameter of 0.71 cm, and a bottom diameter of 0.62 cm. The morphometrics investigated consisted of hatch weight, pupae length, body length, head, abdomen, wing, and hind leg morphometrics. The results showed that the differences in the queen cup size had no effect (P>0.05) on the hatch weight, body length, width, and length of the head, thorax, fore and hind wing (length and width), and abdomen (length and height). The different queen cell sizes did not affect the wing morphometrics (P>0.05). In addition, the leg morphometrics consisting of femur, tibia, tarsus, and metatarsus were also not affected (P>0.05) by the different queen cup sizes. These results revealed that the different queen cup sizes did not negatively impact the morphometric characteristics of A. cerana javana queen’s.